Taşkent (Özbekistan) Zeminlerinin Geotekniği - ÖNALP, AKIN; Duran, İlhan Burak; Duru, Ali Can; MERT, AHMET CAN; AREL, ERSİN (My University, 2019)
Çin’den Bulgaristan’a kadar geniş alanlar lös olarak bilinen topraklarla kaplıdır. Kalınlığı yüzlerce metreye varabilen bu zeminlerin öne çıkan özelliği; suyla karşılaştıklarında gösterdikleri “göçme” davranışıdır. Yüzeysel temellerde ciddi oturma sorunları yaratabilen bu özelliğin değerlendirilmesi lös kuşağında yeralan Özbekistan’ın Taşkent zeminleri için gündeme getirilmiştir. Bu çalışmada kent merkezinde geniş bir adaya yayılacak iş merkezi / rezidans için gerçekleştirilmiş altı farklı zemin inceleme programının sonuçları değerlendirilerek kentte bundan sonra yapılacak yapılaşma çalışmalarına ışık tutulması hedeflenmiştir. Yapılan laboratuvar ve arazi deneyleri Taşkent zemininin lös olarak değerlendirilemeyeceğini göstermektedir.

Vast areas extending from China to Bulgaria are covered by the aeolian sediments called loess which can reach thicknesses up to 300m. Loess deposits can be highly problematic by exhibiting collapse of the structure upon wetting. Uzbekistan is located in the Asian loess belt. A large part in the middle of the capital city of Tashkent is being developed as residential and business centre currently. The findings of six site investigations carried out for the purpose were evaluated in order to shed light on the future construction activities in the city. Extensive laboratory and insitu testing has shown that the silty soil of Tashkent cannot be labelled as loess. The soil classifies as low plasticity clay and exhibits remarkably high parameters. However, the EOP in the consolidation tests were found to extend beyond expected limits, prompting the investigators to scrutinise the results of testing to discover the mechanism behind this property as well as the high magnitude parameters.
Keywords: Loess; Low Plasticity; Compressibility; Parameters; Lös; Düşük Plastisite; Sıkıştırılabilme; Parametreler